Infections in Cirrhosis - Ekpanyapong, Sirina (Curr Treat Options Gastroenterol, 2019)
PURPOSE OF REVIEW: Patients with cirrhosis are at high risk of developing serious infections. Bacterial infections remain the most common cause of morbidity and mortality in these patients. This review is focused on the prevalence of infections in those with cirrhosis, including multidrug-resistant (MDR) pathogens, pathogenesis of infection-related acute-on-chronic liver failure (ACLF), current treatment recommendations, and prophylactic strategies in patients with cirrhosis. RECENT FINDINGS: Recent epidemiological studies have noted an emerging prevalence of MDR bacterial infections and associated with poor prognosis, and a high rate of treatment failure and mortality. Therefore, new recommendations on empirical antibiotic use based on epidemiological data have been developed in order to improve outcomes. SUMMARY: Spontaneous bacterial peritonitis (SBP) and urinary tract infection (UTI) are the most frequent infections followed by pneumonia, cellulitis, and bacteremia, while pneumonia carries the highest risk of mortality. The incidence of MDR bacterial infections has been increasing, especially in healthcare-associated settings. Second infections that develop during hospitalization, multiple organ failures, and high MELD score are associated with poor survival. Preventive measures, early diagnosis, and adequate treatment of infections are essential key concepts in minimizing morbidity and mortality in patients with cirrhosis.